The Effects of Vitamin B-Complex Supplementation on Serum Homocysteine Levels and Migraine Severity in Children A Randomized Controlled Trial: The Effects of Vitamin B-Complex Supplementation on Serum Homocysteine Levels and Migraine Severity in Children A Randomized Controlled Trial - sadeghvand, shahram; barzegar, mohammad; shiva, siamak; Tarmahi , Vahid; Khodaie, Hamed; Rahimi Khamaneh , Elnaz; Golchinfar, Zahra; Raeisi, sina (Iranian Journal of Child Neurology, 2023)
Objectives Given that deficiency in B vitamins can lead to the accumulation of homocysteine (Hcy), and hyperhomocysteinemia may have a role in migraine pathogenesis, the present prospective randomized doubleblinded placebo-controlled trial aimed to evaluate the effect of vitamin B-complex supplementation on the alleviation of migraine in children through a possible reduction in Hcy levels. Materials & Methods Ninety children under 15 years of age suffering from typical migraine were included in the present trial. They were randomly assigned into two groups (forty-five patients in each group) to receive either vitamin B-complex or a matching placebo for six months. Serum Homocysteine levels and headache characteristics were evaluated and compared before and after administering vitamin B-complex or placebo. Results Unlike the placebo group, the monthly headache frequency, severity of headache, headache disability, and serum Hcy levels were significantly decreased after the vitamin administration. The headache duration was not significantly different before and after the treatment. In the vitamin group, there were significant positive correlations between the frequency and severity, frequency and disability, and severity and disability of headaches. Hcy also had significant positive correlations with the frequency and disability of headaches. In the placebo group, the only found significant correlation was between headache frequency and disability Conclusion The administration of vitamin B-complex might effectively relieve migraine severity in children by reducing serum Hcy. However, further studies are needed to confirm the results.